Natur, fortelling og sykdomserfaringer - betydning for opplevelse av livsmot - Bjørg Balteskard (Septentrio Academic Publishing, 2019)
The significance of nature, narratives and illness experiences for our courage to live This essay is based on a description of the live-giving space of nature. The sense of local belonging, the power of narrative and the listener's susceptibility to impressions are live-giving phenomena in a situation where disease threatens. Disease often disrupts the life one wants to live. Narrating is related to one's identity and can help maintain continuity in a life threatened by disease. A new narrative may arise, creating nuanced understanding and recognition of who one is in a changing world. One may thus narrate one's way back into life, rebuild one's identity and rediscover the courage to live. Providing space to tell about the presence of nature can help the ill person towards a renewed experience of being in good places. Time is not bound by illness and may provide relief. Here, the relationship to the narrator is of crucial importance and an impressionable listener is an important sounding board for the one who narrates